Effects of athletic training on physical fitness and stroke velocity in healthy youth and adult tennis players: A systematic review and meta-analysis - Lambrich, Johanna; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2023)
Better physical fitness and stroke velocity in healthy elite compared to sub-elite tennis players have been shown in previous studies. However, evidence-based knowledge regarding the effectiveness of athletic training on physical fitness and stroke velocity is currently lacking. Thus, the objective of this systematic review with meta-analysis was to characterize, aggregate, and quantify athletic training effects on measures of physical fitness and stroke velocity in healthy youth and adult tennis players. A computerized systematic literature search was performed in the databases PubMed, Web of Science, and SportDiscus from their inception date to August 2022. Studies were included, among others, if the intervention period lasted a minimum of four weeks and if at least one parameter of physical fitness (i.e., speed, agility, lower-extremity muscle power, upper-extremity muscle power/strength, endurance, balance, flexibility) or stroke performance (i.e., stroke velocity) was tested. Initially, 11,511 articles were identified, after removing duplicates and assessing abstracts and full texts, 24 articles were used to calculate weighted standardized mean differences (SMD). For measures of physical fitness, athletic training resulted in small (speed: SMD = 0.44), moderate (endurance: SMD = 0.61, upper-extremity muscle power: SMD = 0.72; flexibility: SMD = 0.63), and large (agility: SMD = 0.93, lower-extremity muscle power: SMD = 0.88; upper-extremity muscle strength: SMD = 0.90; balance: SMD = 0.88) effects. Further, a large effect (SMD = 0.90) on stroke velocity was detected. The additionally performed sub-analyses showed differences in the effectiveness of athletic training on variables of physical fitness and stroke speed when considering players' age (i.e., youth players: <18 years; adult players: ≥18 years). Precisely, there was a high potential for training-related adaptations in adult players with respect to lower-extremity muscle power, upper-extremity muscle strength, and stroke velocity and in youth players with respect to endurance. Interventions to promote physical fitness and stroke velocity in healthy tennis players revealed varying levels of effectiveness ranging from small to large and these were additionally affected by players' age. Therefore, future studies should investigate modalities to increase training efficacy in youth and adult tennis players, especially for fitness components that showed small- to moderate-sized changes.